2021
DOI: 10.1055/s-0040-1722255
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Adverse Effects of Tranexamic Acid in Bleeding during Adenotonsillectomy: A Randomized, Controlled, Double-blind Clinical Trial

Abstract: Introduction Intra and postoperative bleeding are the most frequent and feared complications in adenotonsillectomy (AT). Tranexamic acid (TXA), which is known for its antifibrinolytic effects, has a proven benefit in reducing bleeding in hemorrhagic trauma and cardiac surgery; however, the effectiveness and timing of its application in AT have not yet been established. Objectives We aimed to evaluate the efficacy of TXA in controlling bleeding during and after AT and assess its possible adverse effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In our study, local TXA injection did not lead to hemodynamic complications, and no rebleeding occurred. The safety of TXA has been confirmed in previous research on various procedures and conditions 14 , 18 , 22 - 24 . Another finding of the present study was that overall surgeon satisfaction was significantly higher with TXA compared to placebo.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In our study, local TXA injection did not lead to hemodynamic complications, and no rebleeding occurred. The safety of TXA has been confirmed in previous research on various procedures and conditions 14 , 18 , 22 - 24 . Another finding of the present study was that overall surgeon satisfaction was significantly higher with TXA compared to placebo.…”
Section: Discussionsupporting
confidence: 55%
“…Contrarily, 10 mg/kg intravenous TXA did not reduce the bleeding volume in children during adenotonsillectomy 18 . In addition, Soliman et al reported no effect of 15 mg/kg intravenous TXA in decreasing tonsillectomy-related bleeding in pediatric patients 19 .…”
Section: Discussionmentioning
confidence: 80%
“…Full‐text review of these 624 articles was conducted and a total of 71 articles were selected for inclusion (Figure 1). 5,6,8,16‐82 Critical appraisal of studies indicated an acceptably low risk of bias for the majority of included studies (Figure 2A and B). Potential sources of bias were most pronounced in the blinding of participants and personnel, and outcomes in the randomized studies.…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies composed of children with more than 1 indication, 10 found that indication was not related to rates of postoperative bleeding. 29,35,39,40,55,62,70,75,77,82 In 3 studies, the posttonsillectomy hemorrhage rate was higher in the CT/RT group than in the OSA/SDB group 5,6,16 ; however, 2 studies found the opposite to be true. 8 Lou et al reported significantly higher hemorrhage rates in patients with CT/RT than in those with ATH.…”
Section: Discussionmentioning
confidence: 99%